Politik Dalam Persepsi Ulama Kota Palangka Raya - Hakim Syah (Alhadharah: Jurnal Ilmu Dakwah, 2017)
Jurusan Dakwah dan Komunikasi IAIN Palangka RayaElection is manifestation of democracy as stated in constitution. In election, ulama has played a role urgently as opinion leader to direct moslem in voting the candidate. This research aims to know and to describe ulama perception of politic especially Palangka Raya election 2013. The result of research is that ulama has diversity perception on politic and democracy. Their perception is based on attitude, motive, interest, experience, and expectationKeywords: perception, ulama, politic